Cardiac catheterization and coronary intervention - Mitchell, Andrew R. J., 1968-; De Maria, Giovanni Luigi; Banning, Adrian P. (Oxford, United Kingdom ; New York, NY : Oxford University Press, 2020)
"Cardiac catheterization and coronary angiography are both key components to routine cardiology practice. This new edition of Cardiac Catheterization and Coronary Intervention has been fully updated since the first edition, with new sections on primary percutaneous coronary intervention, trends in vascular access, bioabsorbable stents, optical coherence tomography, and more. Filled with over 150 clinical images and schematic illustrations, the handbook is an accessible 'how-to' guide, designed to de-mystify complex cardiac catheterization investigations. Expanded to reflect developments in practice, this new edition also introduces a new chapter on the multidisciplinary team and their roles and responsibilities from pre- to post-procedural care and relevant training requirements. It contains detailed instructions on how to perform a comprehensive left and right heart catheterization procedure, choosing the correct catheter for coronary and graft angiography, and how to perform a diagnostic coronary angiogram and interpret the subsequent findings"--
Includes bibliographical references (page xix) and index.
Keywords: Cardiac catheterization -- Handbooks, manuals, etc; Angiography -- Handbooks, manuals, etc